2010
DOI: 10.1007/s00404-010-1766-9
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of galectin-3 and heparanase in endometrioid and serous carcinomas of the endometrium and correlation with known predictors of survival

Abstract: This investigation suggests that the decreased expression of galectin-3 may be involved in the pathogenesis of endometrial carcinomas from normal endometrium to carcinoma. Also down-regulated stromal expression of galectin-3 in endometrial carcinoma may be involved in lymph node metastasis. Further studies on a larger advanced stage (FIGO stage 3-4) endometrial carcinoma group may determine the value of heparanase in the endometrial carcinoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 45 publications
1
10
0
Order By: Relevance
“…However, no significant difference was found in the heparanase expression in patients with cancer according to prognosis factors. This was also the case for the study by Ege et al, 29 who used the same antibody used in our investigation and were not able to identify differences in the HPSE1 expression comparing the prognosis factors in 64 endometrium carcinomas, except for deep myometrial invasion (P = 0.022). The hypothesis that there might be a difference between the expression of heparanases in glandular and stromal tissue of the endometrium and in different types of nonneoplastic and neoplastic tissues was partially confirmed in this study: the finding of a high frequency of HPSE2 expression in the stromal tissue of women with secretory endometrium is worth highlighting because it might indicate a possible protector role of HPSE2 when secreted in the stroma.…”
Section: Discussionsupporting
confidence: 56%
“…However, no significant difference was found in the heparanase expression in patients with cancer according to prognosis factors. This was also the case for the study by Ege et al, 29 who used the same antibody used in our investigation and were not able to identify differences in the HPSE1 expression comparing the prognosis factors in 64 endometrium carcinomas, except for deep myometrial invasion (P = 0.022). The hypothesis that there might be a difference between the expression of heparanases in glandular and stromal tissue of the endometrium and in different types of nonneoplastic and neoplastic tissues was partially confirmed in this study: the finding of a high frequency of HPSE2 expression in the stromal tissue of women with secretory endometrium is worth highlighting because it might indicate a possible protector role of HPSE2 when secreted in the stroma.…”
Section: Discussionsupporting
confidence: 56%
“…Contradictory to the data by Van den Brule et al [58], Brustmann et al [60] were able to show an increase in galectin-3 in EMCAR samples compared with normal endometrium samples. However, Ege et al [61] reported decreased galectin-3 expression in EMCAR samples compared with normal endometrium. We currently found no increased galectin-1 or galectin-3 expression in tissue lysates of EMCAR or US compared with normal/benign controls.…”
Section: Discussionmentioning
confidence: 99%
“…Galectin-1 is differentially expressed in several tumors in the female reproductive tract. An increased expression of galectin-1 protein is found in endometrial [ 102 , 103 ], breast [ 104 ], ovarian [ 105 ], and cervical [ 106 ] cancers. The intensity of galectin-1 expression also increases according to the pathologic grade of cervical [ 106 ] or breast [ 104 ] cancer and correlates with the depth of invasion of the cervical cancer and in lymph node metastases [ 107 ].…”
Section: Galectins In Tumors Of the Female Reproductive Tractmentioning
confidence: 99%